1, 1‐Carbozirconation: Unusual Reaction of an Alkyne with a Methyl Zirconocene Cation and Subsequent Frustrated Lewis Pair Like Reactivity1. Issue 51 (12th November 2013) - Xu, Xin; Kehr, Gerald; Daniliuc, Constantin G.; Erker, Gerhard
<x xml:space="preserve">Abstract</x> Boron chemistry without the boron: In a reaction analogous to 1, 1‐carboboration, [Cp*2ZrCH3]+ reacts with diphenylphosphino(trimethylsilyl)acetylene by 1, 1‐carbozirconation to give a vicinal [Zr]+/P system. Like B/P frustrated Lewis pairs, the [Zr]+/P system undergoes 1, 2‐addition to unsaturated compounds (including CO2) and reaction with metal complexes and up to three equivalents of CO.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>